2020
DOI: 10.3390/cancers12071730
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Breast Cancer Cell Aggressiveness by lncRNA H19 and its Mir-675 Derivative: Insight into Shared and Different Actions

Abstract: Breast cancer is a major public health problem and the leading world cause of women death by cancer. Both the recurrence and mortality of breast cancer are mainly caused by the formation of metastasis. The long non-coding RNA H19, the precursor of miR-675, is involved in breast cancer development. The aim of this work was to determine the implication but, also, the relative contribution of H19 and miR-675 to the enhancement of breast cancer metastatic potential. We showed that both H19 and miR-675 incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 66 publications
0
25
0
Order By: Relevance
“…In this model, the downregulation of H19 and miR-675 is correlated with the upregulation of IGFR1 (insulin-like growth factor receptor type 1) during neural differentiation [101]. miR-675 action in SCs is transposable in cancer as our team showed that miR-675 expression is associated with that of stem cell marker genes and that this miR is able to enhance stem-like phenotypes such as sphereforming capacity [53]. From a clinical point of view, plasma levels of H19 have been highlighted as predictive markers for breast, stomach, and lung cancers, but also as a way to follow the evolution of cancers [102][103][104].…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…In this model, the downregulation of H19 and miR-675 is correlated with the upregulation of IGFR1 (insulin-like growth factor receptor type 1) during neural differentiation [101]. miR-675 action in SCs is transposable in cancer as our team showed that miR-675 expression is associated with that of stem cell marker genes and that this miR is able to enhance stem-like phenotypes such as sphereforming capacity [53]. From a clinical point of view, plasma levels of H19 have been highlighted as predictive markers for breast, stomach, and lung cancers, but also as a way to follow the evolution of cancers [102][103][104].…”
Section: Discussionmentioning
confidence: 95%
“…In addition, our team recently highlighted a stem cell gene signature (Aldh1a1+; CD44+/CD24−) in breast tumors expressing higher H19. Moreover, these gene signatures were also associated with enhanced H19-derived miR-675 expression, suggesting a role for both H19 and miR-675 in the enrichment of breast CSCs [53].…”
Section: H19 Contributes To the Enrichment And Maintenance Of Cscsmentioning
confidence: 92%
See 1 more Smart Citation
“…For the most part, this is due to the abundance of lncRNAs (more than 50,000 estimated encoded by the human genome) to be studied and their ability to simultaneously act in different cellular pathways with various mechanisms of action [ 139 ]. Among the most well characterised functions, lncRNAs can act in epigenetic regulation, transcriptional and post-transcriptional regulation, miRNA synthesis and function, and protein scaffolding, thereby regulating fundamental cellular processes such as chromatin organisation, cell proliferation and survival, cancer growth, metastasis, and drug resistance [ 140 , 141 , 142 , 143 ]. CSCs play key roles in tumour-associated processes but the mechanisms regulating and maintaining CSC characteristics are largely unknown [ 140 ].…”
Section: Long Noncoding Rnas and Cancer Stem Cellsmentioning
confidence: 99%
“…H19 also promotes sphere formation by pluripotent CSCs produced from human mammary epithelial MCF-10A cells and its expression is associated with reduced disease-free and overall survival in breast cancer patients [ 150 ]. H19 is a precursor of miR-675 and both of these ncRNAs promote breast cancer metastasis via induction of EMT and features of breast CSCs, both in vitro and in vivo [ 141 ].…”
Section: Long Noncoding Rnas and Cancer Stem Cellsmentioning
confidence: 99%